Building Back Better Together: Exploring Community Engagement in Post-Disaster Recovery Efforts - A Review - Ngulube, Nombulelo Kitsepile (Journal of Multidisciplinary Research Advancements, 2024)
Over the past decade, the Build Back Better (BBB) initiative gained traction after the 2004 Indian Ocean Tsunami, aligning with the priorities of the 2015 Sendai Framework for Disaster Risk Reduction (2015-2030). The initiative emphasizes involving “at-risk” communities in recovery efforts to enhance resilience. However, policymakers often neglect community involvement in post-disaster planning, leading to ineffective recovery and reconstruction. The term BBB lacks specificity, necessitating clearer direction. While it outlines principles for rebuilding, it overlooks integrating community participation for successful reconstruction. In this commentary, a comprehensive literature review examines the rebuilding of four case studies: the earthquake and tsunami in Tohoku (Japan), the volcanic eruption in Yogyakarta (Indonesia), Typhoon Yolanda (Philippines), and the Wenchuan Earthquake (China). The author draws upon insights into building back better with community participation. The review highlights how community participation has been embraced in major post-disaster reconstruction projects. It argues that fostering extensive community participation in post-disaster recovery and reconstruction planning and decision-making processes can provide a comprehensive framework for successful recovery initiatives aligned with community expectations. This paper aims to familiarize disaster studies scholars with literature that has received little attention in this field. By so doing, it seeks to refocus the minds of disaster scholars and relevant authorities on the fact that the only way to build back better in post-disaster situations is through engaging with affected communities.